Strategi dan Implementasi Pengembangan dan Pemberdayaan Masyarakat (PPM) PT Bukit Asam (Persero) Tbk., Berbasis Kearifan Lokal dalam Mendukung Keberlanjutan Pertambangan - Taufik Arief; Lusitania; Sri Destita K; Mega Puspita; A.M.M.Rus; Bimbi Cahyaningsih; Eva Oktarinasari; Diana Purbasari; Nina Tanzerina; Rosihan Pebrianto; Eddy Ibrahim; Erwedi (Jurnal Ragam Pengabdian, 2026)
The mining sector is a strategic sector that impacts the environment and local communities. PT Bukit Asam (Persero) Tbk. implements a Community Development and Empowerment (PPM) program to strengthen harmonious relations between the company and surrounding communities, as well as to support sustainable development. Community Service (PKM) activities are carried out through direct visits to partner villages, including Desa Impian, a village established and developed for calliandra cultivation as part of reclamation efforts and as a training center for the surrounding community and former PETI mine employees located in Tanjung Karangan Village, Tanjung Agung Subdistrict, Muara Enim Regency, South Sumatra Province, as well as the Bukit Asam Small Industry Center (SIBA). Located in Tanjung Enim, Lawang Kidul Subdistrict, Muara Enim Regency. The SIBA program serves as the operational hub and primary focus of PT Bukit Asam Tbk’s (PTBA) SME empowerment initiatives.  The Community Engagement Program (PKM) activities, carried out in collaboration with PTBA, aim to identify local potential, assess community needs, conduct outreach, and provide assistance in various sectors, including economic, social, environmental, and educational. The implementation of this PKM program has yielded significant results, including improved harmonious relations with the surrounding community, the creation of economic self-reliance, and sustainable improvements in the quality of life.